2020
DOI: 10.7717/peerj.9024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term continuously monocropped peanut significantly changed the abundance and composition of soil bacterial communities

Abstract: Soil sickness is the progressive loss of soil quality due to continuous monocropping. The bacterial populations are critical to sustaining agroecosystems, but their responses to long-term peanut monocropping have not been determined. In this study, based on a previously constructed gradient of continuous monocropped plots, we tracked the detailed feedback responses of soil bacteria to short- and long-term continuous monocropping of four different peanut varieties using high-throughput sequencing techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
8
8
1
Order By: Relevance
“…Fungi play a key role in decomposition, and the composition of soil fungi community is affected by management and soil nutrient status ( Sui et al, 2019 ). Among the fungi identified in our study, the diversity of fungal communities increased from NCC to CC30 and a similar result was also reported in continuous cropping of vanilla and peanut ( Xiong et al, 2015b ; Chen et al, 2020 ). The dominant phyla of fungi in continuous cropping of sugarcane were Ascomycota, Basidiomycota, and Chytridiomycota, which was consistent with previous studies in continuous cropping of sweet potato and Panax notoginseng ( Tan Y. et al, 2017 ; Gao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Fungi play a key role in decomposition, and the composition of soil fungi community is affected by management and soil nutrient status ( Sui et al, 2019 ). Among the fungi identified in our study, the diversity of fungal communities increased from NCC to CC30 and a similar result was also reported in continuous cropping of vanilla and peanut ( Xiong et al, 2015b ; Chen et al, 2020 ). The dominant phyla of fungi in continuous cropping of sugarcane were Ascomycota, Basidiomycota, and Chytridiomycota, which was consistent with previous studies in continuous cropping of sweet potato and Panax notoginseng ( Tan Y. et al, 2017 ; Gao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, continuous cropping obstacles are caused by complex factors, and the mechanisms remain unclear. Recently, an increasing number of studies have begun to focus on the roles of soil microbial communities in continuous cropping practices ( Xiong et al, 2015b ; Gao et al, 2019 ; Chen et al, 2020 ). Sugarcane, one of the important tropical crops in China, has been planted in monoculture in coastal areas of southern China due to the limited arable land area, which has resulted in soil sickness and significant losses to crop yields could be caused by changes in the microbial composition and soil characteristics ( Miura et al, 2016 ; Kelly et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the relative abundances of Curvibacter and Anaeromyxobacter were greater in unfertilized soils than in fertilized soils (Kumar et al, 2018;Hui et al, 2019). Chen et al (2020) also reported that the relative abundance of the Piscinibacter decreased over a long-term monocropping practice of peanut crops. Our results demonstrated the enrichment of the beneficial bacterial community with unfertilized nature farming.…”
Section: Root Microbial Community Composition Between Unfertilized Nature Farming and Fertilized Conventional Farmingmentioning
confidence: 96%
“…It is a rich source of protein, vitamins, minerals and medicinally active components, such as flavonoids and phenolic compounds (Sui et al, 2018). According to the National Bureau of Statistics of China, peanut crop is being grown on area 4,608 khm2 during 2017 planting season (The National Bureau of Statistics of China, 2018) (Chen et al, 2020). Due to limited arable land and increasing pressure of regional agro-industrialization, large scale peanut monocropping is a common practice in China.…”
Section: Introductionmentioning
confidence: 99%